Development of gallium-doped mesoporous bioactive glass as hemostatic agent / Sara Pourshahrestani - Sara , Pourshahrestani (2017)
Hemorrhage remains the leading cause of potentially survivable death in both military and civilian populations. Although various hemostatic products have been shown to be effective in establishing hemostasis, they remain deficient in a number of desired criteria. An alternative approach to hemostasis is through the application of mesoporous bioactive glasses (MBGs) which can provide a platform to accelerate natural hemostasis and control hemorrhage. However, the materials may not be considered as ideal hemostats since they do not offer antimicrobial activity. The gallium ion (Ga+3) not only exhibits antibacterial properties but may also be effective in the early stage of hemostasis. The main objective of this study was to develop MBGs containing increasing amounts of Ga2O3 (1, 2 & 3 mol %) via the evaporation-induced self-assembly (EISA) process and investigate their potential as hemostatic systems. The physicochemical properties, hemostatic response, antibacterial effect as well as the biocompatibility of the materials were investigated. The second objective of this study was to compare the Ga-MBG determined to have greatest hemostatic efficacy with two commercial hemostats, CeloxTM (CX, Medtrade Products Ltd. Crewe, United Kingdom) and QuikClot Advanced Clotting Sponge PlusTM (ACS+, Z-Medica, Wallingford. Connecticut, USA). The results showed that the inclusion of 1 mol% Ga2O3 content into the MBG system not only resulted in better textural properties (i.e. surface area and pore volume) compared with Ga-free MBG and other substituted glasses, but also increased the release of silicon and calcium ions and degradation rates. The 1%Ga2O3-containing MBG (1%Ga-MBG) was also found to be more effective in inducing blood coagulation, platelet adhesion and thrombus generation as compared to the other Ga2O3-containing MBGs. All experimental MBGs exerted more efficient antibacterial action against both Escherichia coli and Staphylococcus aureus as compared with Ga-free MBG. The results also indicated that antibacterial activity of MBG increased with increase in Ga content in its matrix. Likewise, Ga-doped MBGs showed excellent cytocompatibility with human dermal fibroblast (HDF) cells even after 3 days; particularly the 1%Ga-MBG. No significant differences were found among the 1%Ga-MBG and CX with respect to the numbers of adherent platelets to their surfaces. 1%Ga-MBG activated the intrinsic pathway of coagulation cascade, induce platelet activation, thrombin and thrombus formation more significantly than CX and ACS+. In addition, the 1%Ga-MBG showed higher weight loss in comparison to the CX and ACS+ after 35 days. The results of the cytotoxicity assay demonstrated that all the examined materials were non-cytotoxic to HDF cells after 3 days with the 1%Ga-MBG attaining the higher biocompatibility. Overall, 1%Ga-MBG was found to be superior to CX and ACS+ as it possesses essential factors required for coagulation activation. The results of this study identify 1%Ga-MBG as a promising material platform for designing hemostats for clinical application.